Modern information technologies in tele-medical care for diabetic patients - Bujnowska-Fedak, Maria Magdalena; Puchała, Edward (Przewodnik Lekarza/Guide for GPs, 2009)
The rapid development in information and communication technologies has meant that telemedicine can be used not only in highly specialized clinical units but is becoming a tool available for the patient. A well educated patient, aware of the disease and related consequences, becomes actively involved in the monitoring and treatment process and responsible for collecting, storing and sending medical data to the physician/medical centre. In the paper various kinds of architecture of tele-medical systems used in the process of care in diabetic patients and suitable information technologies are presented. The systematic review of tele-medical systems for diabetic patients shows that they are efficient and have a significant positive effect not only in the clinical aspect but also at the structural, behavioural, informational and economic levels.